Identificação de fatores de virulência e susceptibilidade a antimicrobianos de Staphylococcus aureus isolados de amostras de leites bovino em Minas Gerais - Heleno Fernandes Teles Cardoso (1999)
Staphylococcus aureus has been isolated at high frequency from bovine milk. This microorganism produces a wide variety of vimlence factors, which may contribute to the pathogenicity of this organism. ln this study, 127 S. aureus strains isolated from bovine milk were examined for their productivity of virulence-associated factors and their susceptibility to antimicrobial drugs. The positive rates of the total isolates for various virulence factors were as follows toxic shock syndrome toxin-l (TSST-1) (47,2%) and staphylococcal enterotoxins (SEA-D) (43,3%); ot-haemolysin (43,3%), B-haemolysin (43,3%) and 5-haemolysin (17,3%); tliermostable nuclease (TNase) and coagulase (100%). On the antimicrobial tests 127 (100 %) strains of S. aureus were susceptible to cefotaxime, 125 (98,4%) to gentamicin and enrofloxacin while resistance to ampicillin, penicillin and polymyxin B were most common with 80-82 (62 -64 %) of strains. The results provide evidence that these pathogens use different mechanisms to produce intrammamary infections and their susceptibility to antimicrobial agents should be analyzed.